A CLINICAL STUDY OF NEONATES FROM A TERTIARY CARE TEACHING HOSPITAL IN SOUTHERN HARYANA - SHRADHANG PRATAP GAUTAM; PRIYANKA TANK; ARTI DHINGRA; MEETU YADAV; BABITA KHICHAR; RAKESH TANK (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The present investigation has been undertaken to study certain aspects of neonates clinically at a tertiary care teaching hospital in southern Haryana. Methods: All the patients attending the pediatric department referred from peripheral healthcare facilities to the study site and neonates delivered at the study site formed the study population. Neonates subjected to two or more inter-healthcare facility referrals, neonates with surgical conditions and neonates whose parents/legal caretaker denied consent, were excluded from this study. Results: Among 256 neonates, 59 (23.0%) neonatal sepsis was present out of which 16 (17.8%) were inborn neonates and 43 (25.9%) were outborn neonates. One hundred and ninety-nine (77.7%) neonates were discharged after treatment out of which 76 (84.4%) were inborn neonates and 123 (74.1%) were outborn neonates. One hundred and ninety-nine (77.7%) neonates were discharged after treatment out of which 76 (84.4%) were inborn neonates and 123 (74.1%) were outborn neonates, whereas 40 (15.6%) unfortunately experienced a fatal outcome (death) out of which 9 (10.0%) were inborn neonates and 31 (18.7%) were outborn neonates. Conclusion: Respiratory distress syndrome, neonatal jaundice, and meconium aspiration syndrome are significant contributors to morbidity in newborns. The most prevalent causes of mortality included prematurity, respiratory distress syndrome, birth asphyxia, and sepsis.